Determinants of Vestibular Schwannoma Growth. Issue 5 (June 2021) - Sethi, Mantegh; Borsetto, Daniele; Bance, Manohar; Cho, Yeajoon; Gair, Juliette; Gamazo, Nicola; Joannides, Alexis; Jefferies, Sarah; Mannion, Richard; Macfarlane, Robert; Donnelly, Neil; Tysome, James R.; et al.
Abstract : Objective: Management of vestibular schwannomas (VS) involves surgery, radiotherapy, or surveillance, based on patient and tumor factors. We recently described conditional probability as a more accurate method for stratifying VS growth risk. Building on this, we now describe determinants of VS growth, allowing clinicians to move toward a more personalized approach to growth-risk profiling. Methods: Retrospective analysis of a prospectively collected database in a tertiary referral skull base unit between 2005 and 2014. Inclusion of patients with unilateral VS managed on surveillance protocol for a minimum of 5 years. Analysis of patient age, sex, tumor location, tumor size, and symptomology using conditional probability. Results: A total of 340 patients met inclusion criteria. The conditional probability of growth of extracanalicular VS was significantly higher versus intracanalicular (IC) VS (30% versus 13%, p < 0.001) as was small-sized VS versus IC VS (28 versus 13%, p = 0.002), but only in the first year after diagnosis. Sex, age, and presenting symptoms did not significantly affect VS growth. Conclusion: In our series, extracanalicular VS were more likely to grow than IC VS and small-sized VS more likely to grow than IC VS, but only in the first year after diagnosis. Conversely, sex, age, and presenting symptoms did not affect the conditional probability of VS growth.